Challenges of Gender-Responsive Pedagogy Practices of Teachers - Donna Claire C. Reynales; Lehai B. Beloro (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
The study aimed to determine the influence of challenges on gender-responsive pedagogy (GRP) practices at Central Bicol State University of Agriculture-Sipocot Campus during the school year 2024-2025. This employed a descriptive-correlational method. Statistical analyses included weighted mean, Pearson Product- Moment Correlation Coefficient, and Coefficient of Determination. The data show that teachers are generally in agreement on the issues they face, with an average weighted mean (AWM) of 3.02. Despite challenges, GRP practice was very high, with an average weighted mean (AWM) of 3.65, indicating "very highly practiced." A statistically significant positive correlation was found between the implementation of GRP in course syllabi and challenges in classroom setup (r = 0.383, p < 0.05) and teaching methodology (r = 0.347, p < 0.05). However, there was no substantial link between problems and GRP methods in classroom management or student performance evaluation. The analysis also found very minor connections between course syllabi and classroom arrangement (r2 = 0.15), teaching approach (r2 = 0.12), and gender-neutral language (r2 = 0.01). Similarly, there were weak associations found between classroom management and student performance (r2 values ranged from 0.00 to 0.11). These findings form the basis of a handbook aimed at addressing the stated difficulties.